PENGGUNAAN VIRTUAL REALITY PADA GAME CREED : RISE TO GLORY-CHAMPIONS EDITION DI GAME BLINK PADANG - Tasya Chayrina; Awalia Rahmatia, Adek Kurniawan, Nabila Aprilioni, Vidya Nofriza, Chelsy Putri, Rini Novita (Jurnal Komunikasi, 2024)
The development of Virtual Reality (VR) technology has changed the paradigm in the entertainment industry, especially in the context of games. This research explores the use of VR in the game "Creed: Rise to Glory - Champions Edition" at Game Blink Padang as a case study to understand the impact of VR technology on user experience, local economy, and education. Qualitative research methods were used to analyze user perceptions and the physical and psychological eflects of VR use. The research results show that VR enhances the immersive experience and user satisfaction with the sensation of being deeply present in the virtual environment. Apart from that, the use of VR in Game Blink Padang also has the potential to increase local economic growth through increasing visits and income from technological tourism. The implications of this study include the potential of VR in education and training, as well as challenges such as hardware costs and health issues. These results provide insight into how VR can be a driver of innovation and development of the entertainment industry in the Padang region and its surroundings